Turkic culture in museums of Russia and abroad: Introduction - Zaytuna A. Tychinskikh (Историческая этнология, 2023)
The articles of researchers from Russia and abroad presented on a special topic of the issue of the journal are considered. The issue is dedicated to the richest cultural heritage of the Turkic peoples, stored in the collections of museums. The study and popularization of this heritage is an important and urgent task facing archaeologists, ethnographers, art historians and museologists. The material presented in the issue is a serious contribution of researchers to the further study of the history and culture of the Turkic peoples.